Optimization of SARS-CoV-2 Pseudovirion Production in Lentivirus Backbone With a Novel Liposomal System - Mahalingam, Gokulnath; Rachamalla, Hari Krishnareddy; Arjunan, Porkizhi; Periyasami, Yogapriya; M, Salma; Thangavel, Saravanabhavan; Mohankumar, Kumarasamypet M.; Moorthy, Mahesh; Velayudhan, Shaji R.; Srivastava, Alok; Marepally, Srujan (Frontiers in Pharmacology, 2022)
Due to the fast mutating nature of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the development of novel therapeutics, vaccines and evaluating the efficacies of existing one’s against the mutated strains is critical for containing the virus. Pseudotyped SARS-CoV-2 viruses are proven to be instrumental in evaluating the efficiencies of therapeutics, owing to their ease in application and safety when compared to handling the live virus. However, a comprehensive protocol that includes selecting transfection reagents, validating different packaging systems for high throughput screening of neutralizing antibodies is still a requisite. To this end, we designed and synthesized amide-linker based cationic lipids varying hydrophilic head group from di methyl (Lipo-DME) to methyl, ethyl hydroxyl (Lipo-MeOH) and diethyl hydroxyl (Lipo-DOH) keeping hydrophobic tail, stearic acid as constant. Among the liposomal formulations of these lipids, Lipo-DOH was found to be superior in delivering plasmids and demonstrated comparable transfection efficiencies with commercial standard Lipofectamine 3000. We further used Lipo-DOH for lentivirus and SARS-CoV-2 pseudovirion preparation. Towards comparing different lentivirus packaging systems, we optimized conditions using Addgene and BEI systems and found that the BEI lenti plasmid system was found to be efficient in making lentiviruses using Lipo-DOH. Using the optimized transfection reagent and lentivirus system, we developed a robust protocol for the generation of SARS-CoV-2 pseudovirions and characterized its infectivity in human ACE2 expressing HEK-293T cells and neutralizing properties, IgG against spike protein of SARS-COV-2 positive human sera from individuals recovered from COVID-19